Structural insights of four thermal dissolution products of Dongming lignite by using in-source collision-activated dissociation mass spectrometry. (15th October 2018) - Fan, Xing; Zhang, Xiao-Yun; Dong, Xueming; Liao, Jun-Jie; Zhao, Yun-Peng; Wei, Xian-Yong; Ma, Feng-Yun; Nulahong, Aisha
Abstract: Thermal dissolution (TD) plays an important role in obtaining soluble components from low-rank coals. Characterization of the TD product is essential for both optimization of TD conditions and in-depth understanding of molecular structures in coal that is crucial for the refining processes. In-source collision-activated dissociation (ISCAD) combined with high-resolution mass spectrometry (MS) was employed in this study to analyze four TD products of a low-rank coal obtained by using cyclohexane, acetone, methanol and ethanol as solvents. ISCAD-MS allows the evaluation of distributions of oxygen and nitrogen atoms located within aromatic cores or on alkyl chains based on the abundances of heteroatom-containing precursor ions and fragment ions. In addition, ISCAD-MS can evaluate the abundance of multi-core compounds based on the change of average double bond equivalent value upon fragmentation. These structural details advance the current understanding of the TD products at the molecular level.